Being Smart about Gluten and Gluten-free Issues, Part 2: What Retailers and Consumers Need to Know about Gluten and Gluten-Free Product Labeling - Abigail Dicks; Amy Harder; Amy Simonne (EDIS)
In 2011, gluten was recognized as having a specific link to celiac disease, and some consumers hoping to minimize the symptoms of celiac disease have opted to modify their diets. This is the second of a three-part series of publications called “Being Smart about Gluten and Gluten-Free Issues.” The purpose of this publication is to supply retailers and consumers with easy-to-understand information about labeling as related to gluten-free products. This 3-page fact sheet was written by Abigail Dicks, Amy Harder, and Amy Simonne, and published by the UF Department of Agricultural Education and Communication, September 2013.